Strategi Publik Relations dalam Mengoptimalkan Pengaruh Digital - Fania Alzaira Rahma (Misterius : Publikasi Ilmu Seni dan Desain Komunikasi Visual., 2024)
This research examines the role of public relations (PR) in the digital era, focusing on the relationship between PR and social media, adaptation of communication strategies to technological advancements, and new strategies to enhance digital influence. Through a qualitative literature review approach, this study analyzes relevant literature to identify trends, challenges, and current strategies in PR practice in the digital era. The research findings indicate that social media has become the primary platform for organizations to interact directly with their audience, while adapting communication strategies to technological advancements is crucial in achieving organizational communication goals. Challenges such as the spread of misinformation and online reputation crises are also identified, while new strategies such as storytelling-based content, the use of multimedia platforms, and collaboration with digital influencers are considered crucial steps in enhancing digital influence. This research highlights the importance of openness and transparency in PR practice, as well as the need to continuously adapt communication strategies to technological advancements and user behavior. By understanding and addressing existing challenges, PR practitioners can leverage the opportunities offered by the digital era to strengthen organizational reputation and build strong relationships with their audience.